Hope in the Struggle : A Memoir - Johnson, Josie R., 1930- (Book collections on Project MUSE., 2019)
"Young Black people have repeatedly asked Johnson why she continues to work on social justice issues and how she manages to retain hope. She publishes this book hoping current and future generations will remember the strength of their ancestors, learn from her story, continue the struggle, and gain justice for her people"--